25.7% efficient PERC solar cell using double side silicide on oxide electrostatically doped (SILO-ED) carrier selective contacts: process and device simulation study. (1st May 2023) - Kashyap, Savita; Pandey, Rahul; Madan, Jaya
Abstract: Passivating contacts have recently considered as a superior carrier-selective contact approach for high-efficiency silicon-based photovoltaic devices. However, the conversion efficiencies of the silicon-based passivated emitter and rear cell (PERC) are limited by contact recombination losses that reduce their performance. Therefore, we investigated a new manufacturable silicide on oxide-based electrostatically doped (SILO-ED) carrier-selective contact to suppress the contact recombination losses and reduce the saturation current density ( j 0 ). For the first time, double side electrostatic doping is introduced to the PERC devices to form the carrier selective passivating contacts. First, a conventional PERC device was designed and the effects of surface recombination velocity (SRV) at both contacts were studied. After that, single and double SILO-ED based contacts are introduced into the device and a systematic analysis is performed to understand the tunneling phenomena and improve the conversion efficiency compared to existing PERC cells. The front SILO-ED based device with back contact SRV of 10 cm s −1 showed a power conversion efficiency of 25.4% with j 0 (14.3 fA·cm −2 ). In contrast, the double SILO-ED device delivered 25.7% conversion efficiency by further suppressing the j 0 to 11.8 fA·cm −2 by implementing SILO-ED approach with two different metal silicides such as erbium silicide (ErSi2 ) and palladium silicide (Pd2 Si) on front and rear contact surface. The champion double SILO-ED PERC solar cell delivered a conversion efficiency of 25.7% with an open circuit voltage ( V OC ) of 742 mV. The results reported in this study would help to develop superior passivating contact-based PERC solar cells for higher efficiencies.